Growth Interruptions in Arctic Rhodoliths Correspond to Water Depth and Rhodolith Morphology - Schlüter, Moritz; Pyko, Ines; Wisshak, Max; Schulbert, Christian; Teichert, Sebastian (Minerals (Basel), 2021)
Coralline algae that form rhodoliths are widespread globally and their skeletal growth patterns have been used as (paleo-) environmental proxies in a variety of studies. However, growth interruptions (hiati) within their calcareous skeletons are regarded as problematic in this context. Here we investigated how hiati in the growth of Arctic rhodoliths from the Svalbard archipelago correspond to their environment and morphology. Using X-ray micro-computed tomography and stepwise model selections, we found that rhodoliths from deeper waters are subject to more frequent hiatus formation. In addition, rhodoliths with a higher sphericity (i.e., roundness) are less often affected by such growth interruptions. We conclude that these correlations are mainly regulated by hydrodynamics, because, in deeper waters, rhodoliths are not turned frequently enough to prevent a dieback of coralline algal thalli forming on the underside of the rhodolith. In this coherence, spheroidal rhodoliths are turned more easily, therefore shortening the amount of time between turnover events. Moreover, the incidence of light is more advantageous in shallower waters where rhodoliths exhibit a greater share of their surface to diffused ambient light, thus enabling thallus growth also on the down-facing surface of the rhodoliths. In consequence, information on the frequency of hiatus formation combined with rhodolith morphology might serve as a valuable proxy for (paleo-)environmental reconstructions in respect to light availability and the hydrodynamic regime.